Scientific Social Objects: The Social Objects and Multidimensional Network of the myExperiment Website. - Roure, D; Bechhofer, S; Goble, C; Newman, DR (IEEE, 2011)
Scientific research is increasingly conducted digitally and online, and consequently we are seeing the emergence of new digital objects shared as part of the conduct and discourse of science. These Scientific Social Objects are more than lumps of domain-specific data: they may comprise multiple components which can also be shared separately and independently, and some contain descriptions of scientific processes from which new objects will be generated. Using the myExperiment social website as a case study we explore Scientific Social Objects and discuss their evolution. © 2011 IEEE.